Revealing the mechanism of raw and vinegar-processed Curcuma aromatica Salisb. [Zingiberaceae] regulates primary dysmenorrhea in rats via integrated metabolomics - Su, Lianlin; Tong, Huangjin; Zhang, Jiuba; Hao, Min; Fei, Chenghao; Ji, De; Gu, Wei; Bian, Zhenhua; Mao, Chunqin; Lu, Tulin (Frontiers in Pharmacology, 2022)
Primary dysmenorrhea (PDM) is a common disorder among women around the world. Two processed products of Curcuma aromatica Salisb. [Zingiberaceae] (CAS) are traditional Chinese medicine (TCM) that has long been used to treat gynecological blood stasis syndrome such as primary dysmenorrhea. The mechanisms and active substances of CAS are still largely unknown. The study aimed to establish a rat model of primary dysmenorrhea which investigates the differences between the pharmacodynamics and mechanisms of raw CAS (RCAS) and vinegar-processed CAS (VCAS). Histopathology, cytokinetics and metabolomics were adopted to evaluate anti-blood stasis effect of RCAS and VCAS. In metabolomics, endogenous differential metabolites in plasma, urine and feces are the essential steps to evaluate the effect of RCAS and VCAS. In this study, the rat model of primary dysmenorrhea was successfully established. After RCAS and VCAS intervention, the uterine tissue morphology of dysmenorrhea model rats was improved, and gland hypertrophy and myometrial hyperplasia were reduced as wellvas neutrophils. Compared with RCAS group, the VCAS group had better uterine morphology, less inflammatory factors, and significantly improved amino acid and lipid metabolism. Above results support the conclusion that VCAS performed better than RCAS in primary dysmenorrhea and that vinegar processing increases the efficacy of CAS.